2020
DOI: 10.2478/fv-2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Comparative Diagnostic Study of Anaplasma Spp. Infection in Goats from North-Eastern Algeria

Abstract: Anaplasmosis is an infectious disease affecting goats and other ruminants. Our goal was to estimate the prevalence of Anaplasma spp. infections, and to identify different tick species in goa ts along with their associated risk factors. The epidemiology of Anaplasma spp. (A. ovis/A. marginale) was investigated from April to September 2016 in dairy goats from three different agro-ecological areas in the northeast region of Algeria (Guelma and El-Taref). We tested 182 goat sera using a MSP5 competitive ELISA (cEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
2
2
Order By: Relevance
“…The prevalence of A. ovis infection has previously been reported in small ruminants from central Anatolia [32] and southwestern Anatolia [14] with 31.4% and 60%, respectively, indicating that A. ovis is wide-spread in most regions of Türkiye. Compared to some Mediterranean regions, the prevalence in our study was lower than to the findings previously reported from Tunisia with 70.1% [41], Algeria with 78% [42], Corsica with 52% [12], and Sardinia with 81.8% [43]. Difference in reported prevalence rates may vary depending on many factors such as sampling procedure and size, a standardized assay, sampling season, type of farming, tick infestation status in the herd, and the degree of the exposure to tick vectors [41,42,44].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of A. ovis infection has previously been reported in small ruminants from central Anatolia [32] and southwestern Anatolia [14] with 31.4% and 60%, respectively, indicating that A. ovis is wide-spread in most regions of Türkiye. Compared to some Mediterranean regions, the prevalence in our study was lower than to the findings previously reported from Tunisia with 70.1% [41], Algeria with 78% [42], Corsica with 52% [12], and Sardinia with 81.8% [43]. Difference in reported prevalence rates may vary depending on many factors such as sampling procedure and size, a standardized assay, sampling season, type of farming, tick infestation status in the herd, and the degree of the exposure to tick vectors [41,42,44].…”
Section: Discussioncontrasting
confidence: 92%
“…Compared to some Mediterranean regions, the prevalence in our study was lower than to the findings previously reported from Tunisia with 70.1% [41], Algeria with 78% [42], Corsica with 52% [12], and Sardinia with 81.8% [43]. Difference in reported prevalence rates may vary depending on many factors such as sampling procedure and size, a standardized assay, sampling season, type of farming, tick infestation status in the herd, and the degree of the exposure to tick vectors [41,42,44]. Our finding and the other published data indicate that infections caused by A. ovis are quite common all over the world.…”
Section: Discussioncontrasting
confidence: 92%
“…Several studies have used serological methods to identify reproductive losses associated with T. gondii [ 8 ]. It would be important to use a combination of diagnostic methods, such as histopathological and molecular assays, to identify any association between T. gondii and placental lesions, and to rule out other infectious causes of reproductive disorders [ 59 , 60 ]. In a recent study, the occurrence of Coxiella burnetii in the local goat population in the same study areas was reported [ 61 ], which reflects an exposure of this population to various abortifacient agents, and it should be taken into consideration when applying strategies to prevent and reduce the rate of abortions in goat herds.…”
Section: Discussionmentioning
confidence: 99%
“…Anaplasmosis has a wide host range, including humans, and it is distributed worldwide. The zoonotic potential of some species is of great importance in regards to public health concerns [19,31].…”
Section: Lyme Borreliosis Is Primarily Caused By the Bacteriummentioning
confidence: 99%